Pengaruh Latihan Depth Jump Terhadap Daya Ledak Otot Tungkai Pemain Bola Voli SMK Negeri 3 Bengkulu Selatan - Biy Paidul S; Dolly Apriansyah; Dody Ertanto (Educative Sportive, 2026)
This study aims to determine the effect of depth jump training on the explosive power of leg muscles in volleyball players at SMKN 3 Bengkulu Selatan. A total sampling method was used to determine the number of respondents, resulting in 13 student volleyball players at SMKN 3 Bengkulu Selatan. This experimental study employed a One Group Pretest-Posttest design, a pre-experimental design that includes a pretest (test before treatment) and a posttest (test after treatment) within one group. Data collection used test scores. Descriptive data analysis techniques and t-tests were used. The results of this study indicate an effect of depth jumps on the explosive power of volleyball players at SMKN 3 Bengkulu Selatan, with a calculated t-value of 2.578 and a t-table of 1.782, with a significance level of α = 0.05 and dk = 12.